PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN KUALITAS SISTEM INFORMASI TERHADAP EFEKTIFITAS PENGELOLAAN KEUANGAN DESA - Adam, Rahmi R.; Blongkod, Harun; Aqmal, Ikhlas Ul (Pro-fit, 2024)
This study aims to determine and analyze the competence of human resources and the quality of information systems affect the effectiveness of village financial management. The population of this study were villages in Pohuwato Regency. The sample of this study amounted to 115 respondents. Tests were carried out with descriptive analysis methods using Structural Equation Modeling (SEM) with the help of the Amos 24 program and Statistical Product and Service Solution (SPSS 16). This research proves that human resource competence has a positive and significant effect on the effectiveness of village financial management. Information systems have a positive and significant effect on the effectiveness of village financial management.